2010
DOI: 10.1007/s15010-010-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Device-associated infections in the intensive care units of Cyprus: results of the first national incidence study

Abstract: In comparison to international benchmarks, the markedly high rate of CL-BSI, the high rate of VAP and the resistance patterns of major infecting pathogens identified in this study emphasize the need to improve current practices for appropriate use and management of invasive devices in Cypriot ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
(38 reference statements)
8
14
3
Order By: Relevance
“…The total number of DA-HAIs instances in the third phase (2017), were 87% lower compared to the baseline. In fact DA-HAI incidence rates, especially at the third surveillance period (2017), were much lower than the majority of published literature [8,[37][38][39][40]. After the adjustment for the number of patients, our results confirmed the progressive reduction in both two years that in 2017 was statistically significant.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The total number of DA-HAIs instances in the third phase (2017), were 87% lower compared to the baseline. In fact DA-HAI incidence rates, especially at the third surveillance period (2017), were much lower than the majority of published literature [8,[37][38][39][40]. After the adjustment for the number of patients, our results confirmed the progressive reduction in both two years that in 2017 was statistically significant.…”
Section: Discussionsupporting
confidence: 74%
“…Our interventions resulted to a significant decrease in CLABSI rates from 15.9/1000DD (2015), to 4.2/1000DD (2016) and then to 1.95/1000DD during the 2017 surveillance period (phase three). The absolute 2017 rate appears to be lower than the majority of the reported published literature [5,8,36,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. By the beginning of the next period (2016), our efforts resulted to a significant decrease in CLABSI rates from 15.9/1000DD (2015), to 4.2/1000DD (2016) and then to 1.95/1000DD during the 2017 surveillance period (phase three).…”
Section: Discussionmentioning
confidence: 78%
“…The overall resistance rate to ciprofloxacin observed in the present study was similar to that reported by NNISS but lower than the rate reported by INICC. Gikas et al (17) reported a 22z resistance rate of P. aeuruginosa to ciprofloxacin, whereas Leblebicioglu et al (16) found a rate of 51.1z from the evaluation of 13 ICUs in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…It unfortunately, indicates too rare application of the capabilities of contemporary microbiology in everyday clinical practice of the studied NICUs. This is confirmed by the results of a Cypriot study, in which LC-BSI constituted 96% of all BSIs [23]. Another matter is the debated problem of legitimacy of repeated blood drawing for cultures from VLBW newborns.…”
Section: Discussionmentioning
confidence: 65%